Towards Social Network based Approach for Software Engineering Ontology Sharing and Evolution - Wongthongtham, Pornpit; Chang, Elizabeth; Aseeri, Ahmed (SpringerLink, 2007)
In this paper, we present a multi-agent social network approach that integrates the software engineering ontology and expert recommendation facilities for communities of software engineers remotely working on related software engineering projects. The software engineering ontology enables an active ecology of agents to convey, consume and act on project information (semi) autonomously, according to explicit software engineering domain knowledge. Recommendation techniques are addressed to make progress ? ability to recommend useful project information, solution(s) for project issues that arise as experts.